オウシュウ ヒカンショウ サンラン (EISCAT) レーダー カンソクジョ ノ タハチョウ フォトメータデータ ヲ モチイタ ソウジョウ デンリケン デンドウド ノ スイテイ - 大山, 伸一郎; オオヤマ, シンイチロウ; 渡邉, 太基; ワタナベ, タイキ; 藤井, 良一; フジイ, リョウイチ; 野澤, 悟徳; ノザワ, サトノリ; 津田, 卓雄; ツダ, タクオ; Oyama, Shin-ichiro; Watanabe, Taiki; et al. (2013)
P(論文) 本研究では,多波長フォトメータデータ(427.8 nm, 557.7 nm, 630.0 nm)を利用してオーロラ発生時の高緯度電離圏における電気伝導度推定の手法開発を行った.本手法の特徴は層状の電気伝導度を導出することが可能な点である.この層構造を持つ電気伝導度を光学データから導出するためのモデル関数を,高度分解能がある欧州非干渉散乱(EISCAT)UHF レーダーデータから推定した電気伝導度を用いて決定した.本研究により,電離圏を3 層(高度95-110 km, 110-170 km, 170-300 km)に分割しても,従来の方法と同程度の信頼度を持つ電気伝導度を光学データから導出できることが確認された. This study aimed to develop a methodology for estimating ionospheric conductance at auroral latitudes using data from a multi-wavelength photometer (427.8, 557.7, and 630.0 nm). An advantage of the approach is that the ionosphere is divided into layers and conductance is computed for each layer. From optical data, the layer conductance was determined by using height-resolved conductivity derived from the European Incoherent Scatter (EISCAT) Tromso UHF radar. The developed method can provide conductance from optical data with some confidence (at least at the same level as previous methods) even after separating the ionosphere into three layers, 95-110 km, 110-170 km, and 170-300 km. departmental bulletin paper